Evidence for Pathogen‐Driven Selection Acting on HLA‐DPB1 in Response to Plasmodium falciparum Malaria in West Africa - Thomas Goeury; Ndeye Faye; Pascale Gerbault; Viktor Černý; Eric Crubézy; Jacques Chiaroni; Hacene Brouk; Lydie Brunet; Maxime Galan; Natasja G. deGroot; José Manuel Nunes; Alicia Sanchez‐Mazas (Ecology and Evolution, 2025)
ABSTRACT African populations remain underrepresented in studies of human genetic diversity, despite a growing interest in understanding how they have adapted to the diverse environments they live in. In particular, understanding the genetic basis of immune adaptation to pathogens is of paramount importance in a continent such as Africa, where the burden of infectious diseases is a major public health challenge. In this study, we investigated the molecular variation of four Human Leukocyte Antigens (HLA) class II genes (DRB1, DQA1, DQB1 and DPB1), directly involved in the immune response to parasitic infections, in more than 1000 individuals from 23 populations across North, East, Central and West Africa. By analyzing the HLA molecular diversity of these populations in relation to various geographical, cultural and environmental factors, we identified divergent genetic profiles for several (semi‐)nomadic populations of the Sahel belt as a signature of their unique demography. In addition, we observed significant genetic structuring supporting both substantial geographic and linguistic differentiations within West Africa. Furthermore, neutrality tests suggest balancing selection has been shaping the diversity of these four HLA class II genes, which is consistent with molecular comparisons between HLA genes and their orthologs in chimpanzees (Patr). However, the most striking observation comes from linear modeling, demonstrating that the prevalence of Plasmodium falciparum, the primary pathogen of malaria in Africa, significantly explains a large proportion of the nucleotide diversity observed at the DPB1 gene. DPB1*01:01, a highly frequent allele in Burkinabé populations, is identified as a potential protective allele against malaria, suggesting that strong pathogen‐driven positive selection at this gene has shaped HLA variation in Africa. Additionally, two low‐frequency DRB1 alleles, DRB1*08:06 and DRB1*11:02, also show significant associations with P. falciparum prevalence, supporting resistance to malaria is determined by multigenic and/or multiallelic combinations rather than single allele effects.